Application of the Spiral of Silence Theory in Rural Mojokerto Indonesia: Opininion Contestation in Duck Village and Social Isolation in Leprosy Villagge - Endik Hidayat; Daniel Susilo; Aufa Izzuddin Baihaqi; Rosyidatuzzahro Anisyukurlillah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The background of this study is the hegemony of opinion in the Modopuro duck village and the social isolation of the Sumberglagah leprosy village. This study uses the spiral of silence as the main theory and supports patron-client relationships in rural communities theory. This study took two locations: the Sumberglagah leprosy village in Tangjungkenongo village and the duck village in Modopuro village. This study used a qualitative method focusing on two villages in Mojokerto Regency. This study found the application of the spiral of silence theory applies if public opinion or issues concern villagers' daily lives. Environmental pollution issues in Modopuro and the stigma of the Tanjungkenogo leprosy village are included in the close case category because they are related to the daily life and experiences of the villagers. Another finding is the emergence of patron-client relationships. The position of patrons from business circles with clients in Moduporo villagers is quite strong. Meanwhile, Tanjungkenongo village, which acts as a patron, is a public official for the clients of the villagers, especially the Sumberglagah leprosy village